Incorporation of Magnesium-doped Zinc Oxide (MZO) HRT Layer in Cadmium Telluride (CdTe) Solar Cells - Doroody C.; Sajedur Rahman K.; Chelvanathan P.; Adib Ibrahim M.; Sopian K.; Amin N.; Chowdhury S.; Channumsin S. (Elsevier B.V., 2024)
The insertion of a highly resistive transparent (HRT) layer with the ability to transfer an optimum portion of the UV range of sunlight is targeted in this study by bandgap engineering through varying the thickness as well as the concentration of dopants. The integrability of ZnO and Mg-doped ZnO (MZO) as the potential HRT layers for CdTe solar cell devices with the possibility of bandgap management, high transmission at short wavelength and reduced current loss by inhibiting holes from reaching interfacial defects is proposed. Using SCAPS-1D modelling software, key performance parameters such as open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF), conversion efficiency (?), and quantum efficiency (QE) were evaluated for the proposed devices by varying the carrier concentration and series resistance (Rs). The simulation was carried out based on experimental data such as thickness, optical characteristics and bandgap to validate the findings. Results showed that the conversion efficiency for thin-film solar cells of ITO/CdS/CdTe, ITO/ZnO/CdS/CdTe and ITO/MZO/CdS/CdTe were attained to be 17.83%, 18.76% and 20.27%, respectively. The optimal carrier concentration using ZnO, and MZO was found to be 1016 cm?3 for an efficient CdTe solar cells design. 2023